2020
DOI: 10.1115/1.4048740
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Additive Manufacturing of Ambient Pressure-Dried Silica Aerogel

Abstract: The conventional manufacturing processes of aerogel insulation material is largely relying on the supercritical drying, which suffers from issues of massive energy consumption, high-cost equipment, and prolonged processing time. With the consideration of large market demand of the aerogel insulation material in the next decade, a low-cost and scalable fabrication technique is highly desired. In this paper, a direct ink writing (DIW) method is used to three-dimensionally fabricate the silica aerogel insulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…A previous study showed that the flexible composite has a compressive strength of 2.19 MPa, while the additive manufactured composite with 20 wt % fiber has a tensile strength of 15.84 MPa. 15,32 When the aerogel concentration is below 30 wt %, the slip between fibers would cause the bun seal curves, and for the sample with an aerogel concentration bigger than 30 wt %, the porous silica aggregates and fiber framework becomes a integrate porous solid with a higher density, so the maximum strength increases significantly.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A previous study showed that the flexible composite has a compressive strength of 2.19 MPa, while the additive manufactured composite with 20 wt % fiber has a tensile strength of 15.84 MPa. 15,32 When the aerogel concentration is below 30 wt %, the slip between fibers would cause the bun seal curves, and for the sample with an aerogel concentration bigger than 30 wt %, the porous silica aggregates and fiber framework becomes a integrate porous solid with a higher density, so the maximum strength increases significantly.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The surface roughness was decreased from 7 µm to 0.155 µm with the MAF method. Guo et al [137] presented an experimental and analytical study on the internal surface quality improvement of Inconel 718 by abrasive flow machining (AFM). The results showed that good surface quality can be achieved with low extrusion pressure, high viscosity, low temperature, and large particle size.…”
Section: Machining and Abrasive Finishingmentioning
confidence: 99%
“…at a low cost, using an ambient pressure drying approach. Currently, the most commonly used methods for measuring ambient pressure are: Network reinforcement and solvent exchange are two aspects of drying (Guo et al, 2021). Wet gels have a surface modified by (Chandradass, Kang, & Bae, 2008;Rao, Nilsen, & Einarsrud, 2001;Shi, Wang, & Liu, 2006).…”
Section: Introductionmentioning
confidence: 99%